2014
DOI: 10.1155/2014/560620
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Induced Endotoxemia in Pediatric Nonalcoholic Fatty Liver Disease

Abstract: In preclinical studies of fructose-induced NAFLD, endotoxin appears to play an important role. We retrospectively examined samples from three pediatric cohorts (1) to investigate whether endotoxemia is associated with the presence of hepatic steatosis; (2) to evaluate postprandial endotoxin levels in response to fructose beverage in an acute 24-hour feeding challenge, and (3) to determine the change of fasting endotoxin amounts in a 4-week randomized controlled trial comparing fructose to glucose beverages in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 34 publications
(42 reference statements)
0
61
0
1
Order By: Relevance
“…Consistent with the animal models, several recent studies have reported elevated levels of blood endotoxin in adult patients with simple steatosis and NASH [38, 39], as well as in children with NAFLD [40, 41]. Intestinal permeability was correlated with the liver disease severity; specifically, intestinal permeability was increased in children with steatohepatitis compared to those with steatosis only [42].…”
Section: Nafld: Gut Barrier Endotoxemia and Dietary Factorsmentioning
confidence: 68%
“…Consistent with the animal models, several recent studies have reported elevated levels of blood endotoxin in adult patients with simple steatosis and NASH [38, 39], as well as in children with NAFLD [40, 41]. Intestinal permeability was correlated with the liver disease severity; specifically, intestinal permeability was increased in children with steatohepatitis compared to those with steatosis only [42].…”
Section: Nafld: Gut Barrier Endotoxemia and Dietary Factorsmentioning
confidence: 68%
“…Indeed, the administration of antibiotics to reduce the endotoxemia can improve the fatty liver (88, 89). Endotoxemia has also been shown to be elevated in children with NAFLD (91). Thus, the microbiome may have a role in fructose-induced fatty liver through an interaction with fructose metabolism in the intestinal wall.…”
Section: Fructokinase the Principal Enzyme Driving Fructose-induced mentioning
confidence: 99%
“…Gut wall integrity and the intestinal microbiome are impaired by high-fat and high-sugar diets commonly consumed by the obese (106)(107)(108). Evidence points to the importance of fiber, its metabolites, and other dietary components (106,(109)(110)(111) in maintaining a healthy gut barrier (112,113) and intestinal microbiome (114) to prevent diet-induced chronic inflammation and insulin resistance (84,106,115).…”
Section: Gut Wall Integritymentioning
confidence: 99%